Từ PT thứ hai $\Rightarrow 4x^{2}-22x+21=4y+3, thay và PT thứ nhất ta đượcy^3+3y^2+5y+3=(2x+1)\sqrt{2x-1}\Leftrightarrow (y+1)(y^2+2y+3)=(2x+1)\sqrt{2x-1}Đặt f(t)=t(t^2+2) thì PT trên \Leftrightarrow f(y+1)=f(\sqrt{2x-1})Ta có f'(t)=3t^2+2>0 \quad \forall t nên f$ là hàm đồng biến, suy ra $y+1=\sqrt{2x-1}\Rightarrow 2x^{2}-11x+11=2y +2=2\sqrt{2x-1}\Rightarrow 2x^{2}-11x+11=2\sqrt{2x-1} $\Rightarrow (2x^{2}-11x+11)^2=4(2x-1)\Rightarrow (x-1)(x-5)(2x-5)^2=0Từ đấy thu được: (x,y) \in \left\{ {(1,0), (5,2),(5/2,1)} \right\}Thử lại chỉ có \color{green}{(x,y) \in \left\{ {(1,0), (5,2)} \right\}}
\bigstar
Từ PT thứ hai $\ Rightarrow 4x^{2}-22x+21=4y+3, thay và PT thứ nhất ta đượcy^3+3y^2+5y+3=(2x+1)\sqrt{2x-1}\Leftrightarrow (y+1)(y^2+2y+3)=(2x+1)\sqrt{2x-1}Đặt f(t)=t(t^2+2) thì PT trên \Leftrightarrow f(y+1)=f(\sqrt{2x-1})Ta có f'(t)=3t^2+2>0 \quad \forall t nên f$ là hàm đồng bi ến, suy ra $y+1=\sqrt{2x-1}\Rig htarrow 2x^{2}-11x+11=2y +2=2\s qrt{2x-1}\Rightar row 2x^{2}-11x+11=2\sqrt{2x-1} $ \Rightarrow (2x^{2}-11x+11)^2=4(2x-1)\Rightarrow (x-1)(x-5)(2x-5)^2=0Từ đấy thu được: (x,y) \in \left\{ {(1,0), (5,2),(5/2,1)} \right\}Thử lại chỉ có \color{green}{(x,y) \in \left\{ {(1,0), (5,2)} \right\}}
|